SERVQUAL study on the traditional chinese medicine industry in Singapore - Ang, Hui Teng (2008)
This study investigates the service quality of Traditional Chinese Medicine clinics in Singapore, through the use of SERVQUAL model by focusing on Gap 5 of the Gap Analysis Model. A Service Blueprint using an example of a TCM clinic, will help to gain further insights into the service quality and process of the industry. The findings show that the perceived service at local TCM clinics exceeds the minimum expectation. Thus, this allows us to look into areas to improve on the service level to minimise Gap 5 and strive for better service excellence.